2010
DOI: 10.12968/ijpn.2010.16.5.48143
|View full text |Cite
|
Sign up to set email alerts
|

Community nurses’ experiences of ethical dilemmas in palliative care: a Swedish study

Abstract: The study confirms the need for knowledge about how community nurses experience dilemmas in ethical decision-making. They have the freedom to act and the willingness to make decisions, but they lack competence and knowledge about how their colleagues' experience and deal with such issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 27 publications
3
44
0
Order By: Relevance
“…Nurses who provide end‐of‐life care in the patient's own home often felt ill at ease and powerless in their work when dealing with conflicts in the family .This is in line with Karlsson et al. , who found that community nurses experienced powerlessness, frustration and concern in relation to ethical dilemmas in end‐of‐life care in the patient's own home. The nurses felt powerless when they did everything possible, but the patient's relatives placed still higher demands on them that they were unable to fulfil.…”
Section: Introductionsupporting
confidence: 70%
“…Nurses who provide end‐of‐life care in the patient's own home often felt ill at ease and powerless in their work when dealing with conflicts in the family .This is in line with Karlsson et al. , who found that community nurses experienced powerlessness, frustration and concern in relation to ethical dilemmas in end‐of‐life care in the patient's own home. The nurses felt powerless when they did everything possible, but the patient's relatives placed still higher demands on them that they were unable to fulfil.…”
Section: Introductionsupporting
confidence: 70%
“…1,2,5,[8][9][10][11][12] Leuter and colleagues 11 found that most nurses experienced recurrent ethical problems and did not feel effectively supported by the health care system. These include futile or nonbeneficial care, pain management, patient autonomy (lack of decisional capacity, patient confidentiality or privacy), advance care planning (disregard of patients' wishes), communication difficulties, conflicts between patients/families and health providers, and conflicts between nurses and colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study confirms that the meeting with the dying patient forces the nurse to deal with existential questions about the meaning of life. [38] The interviewed nurses stressed the value of developing one's communication skills in relation to the patient and relatives. According to Karlsson and Sandén, [39] good palliative caring demands successful communication and a good relationship with the patient and relatives.…”
Section: Discussionmentioning
confidence: 99%